PERBANDINGAN PENDIDIKAN AGAMA ISLAM DI INDONESIA STUDI PADA MADRASAH, SEKOLAH UMUM, DAN PESANTREN - Razelia, Zaskya Putri; Husna, Nabilatul; Febrianti, Lara; Ilham, Ijratil; Ahmad, Aprizal (Cahaya Ilmu Bangsa Institute, 2025)
Islamic education plays a crucial role in shaping the moral and intellectual character of Muslim societies around the world. This study aims to compare the development, curriculum policies, and implementation of Islamic education systems in Indonesia and Egypt. Indonesia's Islamic education system has evolved from traditional institutions such as pesantren and madrasah into modern, integrated educational models aligned with the national education system. Meanwhile, Egypt, through the influence of Al-Azhar University, has established a centralized and structured Islamic education framework that strongly emphasizes religious sciences and teacher quality. The comparison reveals similarities in the objectives of moral and spiritual formation, yet differences lie in historical backgrounds, curriculum design, infrastructure equity, and government support. Indonesia’s challenge remains in professional management and equitable distribution of educational resources, while Egypt maintains stronger state involvement and curriculum uniformity. The study concludes that both nations play strategic roles in promoting moderate, inclusive, and globally competitive Islamic education, with the need for continuous collaboration and innovation to address the challenges of modernization and globalization. Keywords: Islamic education, curriculum, Indonesia, Egypt, comparison, modernization. Abstrak Pendidikan Agama Islam memiliki peran penting dalam membentuk karakter, moral, serta identitas keagamaan masyarakat muslim di berbagai negara. Indonesia dan Mesir merupakan dua negara dengan mayoritas penduduk muslim yang menjadikan pendidikan Islam sebagai bagian utama dari sistem pendidikan nasionalnya. Artikel ini membahas perkembangan, kebijakan, dan sistem pendidikan Islam di Indonesia serta membandingkannya dengan sistem pendidikan Islam di Mesir. Hasil analisis menunjukkan bahwa meskipun kedua negara memiliki dasar dan tujuan yang sama, namun terdapat perbedaan dalam kebijakan, kurikulum, metode pembelajaran, serta pemerataan sarana pendidikan. Kata Kunci: Pendidikan Agama Islam, Indonesia, Mesir, Kurikulum, Pesantren, Al-Azhar.